PEMILIHAN JENIS PERMAINAN PADA ANAK USIA 10-14 TAHUN DI KELURAHAN PADANG TERUBUK KECAMATAN SENAPELAN KOTA PEKANBARU - Santi Safitri; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The background of this study comes from the author's observation of playing activities in children aged 10-14 years that I observe in life today in the Padang Terubuk Sub-District, Senapelan District, Pekanbaru City. Padang Terubuk Village, Senapelan Sub-District, Pekanbaru City and any social characteristics related to the choice of type of game in children aged 10-14 years in the Padang Terubuk Sub-District, Senapelan District, Pekanbaru City. The purpose of this study was to find out how the form of play activity and any social characteristics related to the selection of types of games in children aged 10-14 years in the Kelurahan Padang Terubuk, Senapelan District, Pekanbaru City. This study uses descriptive quantitative research methods, the population in this study were all children aged 10-14 years in Padang Terubuk Sub-District. The sample in this study amounted to 81 people determining the sample obtained from using the Slovin formula. The results showed that the form of game activities carried out by children based on the results of the author's research was in the form of sports games, traditional games, and modern games, where the authors concluded that the most common sports game was bicycle sports or 33.3 % while the most commonly played traditional games are games / single cards at 12.3% while those of the modern games that are most frequently played by respondents in this study are online game play or 32.1%, social characteristics that are related to the choice of type of game among children is among them due to factors such as age, gender, playmates, and also school time. Keywords: children, games, elections.